NORMALISASI LANSKAP KORIDOR SUNGAI MATI CITARUM DENGAN ANALISIS HIDROLOGI (Studi Kasus: Desa Rancamanyar, Kabupaten Bandung) - Izzati, Husna; Rustandi, Iing (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2025)
The Citarum River is the main river in West Java and serves ecological, economic, and hydrological functions. Unfortunately, the river basin, which is located near residential and industrial areas such as households, agriculture, livestock, and textile industries, has been heavily impacted by pollution. The causes of this pollution include factory waste, sedimentation, garbage accumulation, riverbank clearing, and a lack of public awareness. Efforts to manage the river basin have involved straightening the river body to reduce pollutant accumulation, but this has led to the creation of old river bodies known as dead rivers or oxbows. Oxbows face problems such as waterlogging, poor sanitation, unauthorized land acquisition, and social conflicts. A study was conducted to identify hydrological problems in the oxbow landscape, particularly in Rancamanyar, Baleendah, Bandung Regency. The study used a combination of qualitative data obtained through observation and interviews, as well as quantitative data from rainfall, flow rate, and oxbow storage. Analysis of the data was carried out using descriptive methods, formulas, and software. The study found that the flow entering the oxbow and the level of rainfall affect the flood cycle in the area around the Rancamanyar Oxbow. By calculating estimated planned flood discharge, inflow and outflow discharge, and the maximum capacity of the oxbow, the study determined the ideal span shape of the oxbow cross-section, which serves as the basis for normalizing the landscape of Rancamanyar Oxbow.